Neuroendocrine-immune relationships at rats regardless of sex and exposure to stressors or adaptogens - Oleksandr Plyska; Alyona Vorobienko; Roman Yanchii; Xawery Żukow (Journal of Education, Health and Sport, 2023)
Introduction and aim. Since the discovery of the famous Selye triad, studies of the connections between adaptation hormones and the immune system have remained relevant. We formulated the aim of the future study: in the mode of synchronicity, to reveal sexual differences in the parameters of the neuroendocrine-immune complex and the state of neuroendocrine-immune relationships in intact rats and exposed to stressors and adaptogens. This article initiates the beginning of the movement towards achieving the goal.